1997
DOI: 10.1074/jbc.272.26.16206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg(II) Binding on the Structure and Activity ofEscherichia coli DNA Topoisomerase I

Abstract: Escherichia coli DNA topoisomerase I is the best characterized bacterial type I DNA topoisomerases (for review, see Refs. 1 and 2). Its major function in vivo is the removal of negative supercoils from DNA (3, 4). In vitro, such relaxation activity requires that Mg(II) be present in the reaction mixture (3, 5).When other divalent ions were tested (5), Ca(II) could partly replace the Mg(II) in the relaxation of negatively supercoiled DNA while the presence of other divalent ions, such as Mn(II), did not support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 14 publications
5
39
2
Order By: Relevance
“…Double and triple mutants lacking two or more of these acidic residues have now been purified for analysis of their enzymatic activities. The results presented here showed that relaxation activity for double mutants involving Asp-111, Asp-113, and Glu-115 requires higher concentrations of Mg(II) for maximal activity, supporting the hypothesis that the carboxylates in these three conserved acidic residues are involved in coordinating at least one of the two Mg(II) required for relaxation activity (13). We have also developed a proteolytic digestion assay using Glu-C endoproteinase to detect the Mg(II)-induced conformational change in E. coli DNA topoisomerase I.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…Double and triple mutants lacking two or more of these acidic residues have now been purified for analysis of their enzymatic activities. The results presented here showed that relaxation activity for double mutants involving Asp-111, Asp-113, and Glu-115 requires higher concentrations of Mg(II) for maximal activity, supporting the hypothesis that the carboxylates in these three conserved acidic residues are involved in coordinating at least one of the two Mg(II) required for relaxation activity (13). We have also developed a proteolytic digestion assay using Glu-C endoproteinase to detect the Mg(II)-induced conformational change in E. coli DNA topoisomerase I.…”
supporting
confidence: 61%
“…We have previously shown that following incubation of the wild type topoisomerase I with 2 mM MgCl 2 , around 2 Mg(II) remains bound to each enzyme molecule after dialysis (13). Similar treatment of the acidic triad double and triple mutants followed by inductively coupled plasma analysis of the Mg(II) content (Table I) showed that their Mg(II) binding stoichiometries were reduced, in correlation with the relaxation activities observed.…”
Section: Double and Triple Mutants-mentioning
confidence: 74%
See 2 more Smart Citations
“…ATP±Mg) [6,7]. The third mechanism is through allosteric activation in which binding to one or www.elsevier.com/locate/ijbcb more forms of the enzyme in the reaction course induces a change in its conformation [8,9].…”
Section: Introductionmentioning
confidence: 99%